2000
DOI: 10.1093/jat/24.6.442
|View full text |Cite
|
Sign up to set email alerts
|

Total Morphine Stability in Urine Specimens Stored under Various Conditions

Abstract: The stability of total morphine in urine stored under various conditions was studied using control and experimental specimens. Samples in the control group were prepared using drug-free urine spiked with morphine at three concentration levels (300, 1000, and 2500 ng/mL), each with the pH adjusted to 5.5, 6.5, and 7.5. Samples in the experimental group came from 20 alleged heroin addicts (provided by Taipei Municipal Psychiatric Hospital). Samples in both groups were divided into two categories--one with and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Morphine mean recoveries + SEM were 95 • 0.3%, 100 • 0.5% and 102 • 0.2%, respectively. This agreed with previously reported Time (h) studies (25). 6-AM recoveries were 12 + 1%, 21 • 0.6%, and 106…”
Section: To 6h With a Median Of 24 H For The Lower Dose Group And 2supporting
confidence: 92%
“…Morphine mean recoveries + SEM were 95 • 0.3%, 100 • 0.5% and 102 • 0.2%, respectively. This agreed with previously reported Time (h) studies (25). 6-AM recoveries were 12 + 1%, 21 • 0.6%, and 106…”
Section: To 6h With a Median Of 24 H For The Lower Dose Group And 2supporting
confidence: 92%
“…This issue increased the interest of toxicological laboratories to ensure that analyte instability will not affect analytical results during the retesting period. A large body of data is available on the stability in urine of phencyclidine [7][8][9], lysergic acid diethylamide [9][10][11][12][13], cannabinoids [8][9][10][11][12][13][14][15][16][17][18][19][20], morphine and codeine [8,9,17,[21][22][23][24][25][26], and cocaine/benzoylecgonine [8,10,15,17,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Only the identification of 6‐acetyl‐morphine in biological samples provides unequivocal proof of heroin use . Several studies have been reported concerning the stability of opiates in different biological samples, for example, plasma, serum, or blood , urine , hair , and oral fluids , but some factors have not been fully addressed. The purpose of this study was to investigate the effects of the type of sampling tubes, the addition of preservative and the type of anticoagulant on the stability of morphine, codeine, and especially 6‐acetyl‐morphine in blood samples.…”
mentioning
confidence: 99%